Receiving Nodes Selection Algorithm for Improving TDOA-Based Location Estimation Accuracy in Swarm Drone Operation Environments - Kim, Jisoo; Choi, Seonjoo; Lim, Jaesung (2022 International Conference on Electronics, Information, and Communication, ICEIC 2022, 2022)
In this study, we propose an algorithm for selecting nodes with the minimum dilution of precision (DOP) to improve the accuracy of estimating the location of an unknown signal source in a swarm drone environment. The pulse radar emits a narrow beam, and the swarm drones receive the emitted pulses at different times. The ground control station derives the time difference between the received signals based on the PRI. For accurate location estimation of the signal source using time difference of arrival (TDOA), a plane perpendicular to the vector connecting the estimated location coordinates of the signal source and center of gravity of the swarm drone is determined. The swarm drones are orthogonally projected on the determined plane, and a reference node that can reduce the DOP is selected by dividing the plane. Then, the location of the TDOA-based signal source is estimated by selecting a set of nodes that forms the minimum DOP with the reference node. The receiving nodes with the minimum DOP were selected among the deployed swarm drones, and it was confirmed using MATLAB simulation to effectively estimate the location of the signal source.
Keywords: Dilution of precision; Location estimation; Node selection algorithms; Receiving nodes; Reference nodes; Relay; Signal source; Swarm drone; Time-difference-of-arrival; TOA; DOP; Location Estimation; Relay; Swarm Drone; TDOA; TOA